PENGUATAN RENCANA STRATEGIS PENGEMBANGAN DESA WISATA (STUDI KASUS DESA GIRI SASAK, KECAMATAN KURIPAN) - Made Suarni; Animah Animah; Lalu Takdir Jumaidi (Universitas Muhammadiyah Jember, 2022)
This research aims to analyze the strategic plan (Renstra) of the development of Bukit Batu Gendang tourist attraction, strengthen the strategic plan, the role of government and community participation. The location of this research is Bukit Batu Gendang which located in Buntage and Lendang Sedi Hamlate, Giri Sasak Village Kuripan District of West Lombok Regency. This research uses a qualitative research approach with case study design. The data collection methods used are observation, interviews and documentation. There are two grand theories that are the basis of this research, namely Theory of Constrain and Participant Theory. Theory of constrain is used as a foundation in solving the problems faced and Participant Theory is used as a reference in the analysis of community participation. SOAR analysis is used to devise alternative strategies that will then be used to reinforce existing plans. The results of the study show that 1) The strategic plan that has been made has not led specifically to the development of tourist attractions and there are some realizations of plans that are not in accordance with those listed in the RPJMDes. 2) There are 11 alternative strategies produced to strengthen the strategic plan of development of tourist villages, especially Bukit Batu Gendang tourist attractions. 3) The Giri Sasak Village Government has carried out its role well started from planning to supervision and there are several types of participation given by the community, namely intensive participation and participation for material incentives.